Peptide and Lipid Modulation of Glutamatergic Afferent Synaptic Transmission in the Solitary Tract Nucleus - Andresen, Michael C.; Fawley, Jessica A.; Hofmann, Mackenzie E. (Frontiers in Neuroscience, 2013)
The brainstem nucleus of the solitary tract (NTS) holds the first central neurons in major homeostatic reflex pathways. These homeostatic reflexes regulate and coordinate multiple organ systems from gastrointestinal to cardiopulmonary functions. The core of many of these pathways arise from cranial visceral afferent neurons that enter the brain as the solitary tract (ST) with more than two-thirds arising from the gastrointestinal system. About one quarter of ST afferents have myelinated axons but the majority are classed as unmyelinated C-fibers. All ST afferents release the fast neurotransmitter glutamate with remarkably similar, high-probability release characteristics. Second order NTS neurons receive surprisingly limited primary afferent information with one or two individual inputs converging on single second order NTS neurons. A- and C-fiber afferents never mix at NTS second order neurons. Many transmitters modify the basic glutamatergic excitatory postsynaptic current (EPSC) often by reducing glutamate release or interrupting terminal depolarization. Thus, a distinguishing feature of ST transmission is presynaptic expression of G-protein coupled receptors for peptides common to peripheral or forebrain (e.g. hypothalamus) neuron sources. Presynaptic receptors for angiotensin (AT1), vasopressin (V1a), oxytocin (OT), opioid (MOR), ghrelin (GHSR1) and cholecystokinin (CCK) differentially control glutamate release on particular subsets of neurons with most other ST afferents unaffected. Lastly, lipid-like signals are transduced by two key ST presynaptic receptors, the transient receptor potential vanilloid type 1 (TRPV1) and the cannabinoid receptor (CB1) that oppositely control glutamate release. Increasing evidence suggests that peripheral nervous signaling mechanisms are repurposed at central terminals to control excitation and are major sites of signal integration of peripheral and central inputs particularly from the hypothalamus.